Perioperative management of a morbidly obese pregnant patient undergoing cesarean section under general anesthesia - case report - Benevides,Márcio Luiz (2016)
Abstract Background and objectives: The increased prevalence of obesity in the general population extends to women of reproductive age. The aim of this study is to report the perioperative management of a morbidly obese pregnant woman, body mass index >50 kg/m2, who underwent cesarean section under general anesthesia. Case report: Pregnant woman in labor, 35 years of age, body mass index 59.8 kg/m2. Cesarean section was indicated due to the presumed fetal macrosomia. The patient refused spinal anesthesia. She was placed in the ramp position with cushions from back to head to facilitate tracheal intubation. Another cushion was placed on top of the right gluteus to create an angle of approximately 15° to the operating table. Immediately before induction of anesthesia, asepsis was carried out and sterile surgical fields were placed. Anesthesia was induced in rapid sequence, with Sellick maneuver and administration of remifentanil, propofol, and succinilcolina. Intubation was performed using a gum elastic bougie, and anesthesia was maintained with sevoflurane and remifentanil. The interval between skin incision and fetal extraction was 21 min, with the use of a Simpson's forceps scoop to assist in the extraction. The patient gave birth to a newborn weighing 4850 g, with Apgar scores of 2 in the 1st minute (received positive pressure ventilation by mask for about 2 min) and 8 in the 5th minute. The patient was extubated uneventfully. Multimodal analgesia and prophylaxis of nausea and vomiting was performed. Mother and newborn were discharged on the 4th postoperative day.